Developing Internet Protocol Television and Future Broadcasting Platforms: A Literature Review - Sheehan, Maree (Te Kaharoa, 2011)
The purpose of this literature review is to examine fundamental research that has been undertaken in the field of Internet protocols. It will look at technology, cultural knowledge, and economic factors for Māori in order to explore the development of Internet protocol television (IPTV) and future broadcasting platforms.Furthermore, this review seeks to obtain relevant information and research in order to critically appraise studies and directly use the information to identify relevant areas for Māori; formulate questions for further research into the development of IPTV and future broadcasting and to synthesise the results in a summary to demonstrate what is known and what is not known about the development of IPTV for Māori.